Further Thoughts on Depreciation and the Rate Base - May, George O. (Quarterly Journal of Economics, 1930)
Further Thoughts on Depreciation and the Rate Base Get access George O. May George O. May Price, Waterhouse & Co., New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 4, August 1930, Pages 687–697, https://doi.org/10.2307/1884030 Published: 01 August 1930